The Trickster Figure in Queer YA: A Case Study of Margaret Owen’s Little Thieves - Alex Henderson (Leaf Journal, 2025)
As scholars such as Helena Bassil-Morozow have explored, the trickster character type—with its roots in mythology, folklore, and oral storytelling traditions—has been constantly reinvented and remixed in the context of contemporary literature and pop culture. The themes of liminality, marginality, shape-changing, and questioning authority with a playful and rebellious sense of humour, mean that the trickster may be especially at home in work aimed at adolescent readers, particularly those of marginalised identities. The emerging space of queer Young Adult (YA) literature is thus a vibrant storytelling landscape for trickster characters and trickster tales.